The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1097/prs.0000000000003868
|View full text |Cite
|
Sign up to set email alerts
|

Optimization and Standardization of the Immunodeficient Mouse Model for Assessing Fat Grafting Outcomes

Abstract: Human fat graft retention in the immunodeficient mouse correlates with graft viability in small, 0.3-ml-volume grafts. However, centralized oil cysts in nonviable 1.0-ml grafts were not resorbed by 18 weeks and thus volume measurements were confounded and not significantly different from viable samples. In addition, tissue injury scores increased in initially healthy fat grafts at 18 weeks, possibly because of a delayed immune reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 18 publications
1
1
1
Order By: Relevance
“…1). In the current study, a decrease in graft size from 2 to 12 weeks was observed in all groups, which was consistent with other studies [28, 29]. The absorption period of dead adipocytes by macrophage phagocytosis within 3 months after transplantation accounts for the atrophy of the grafted fat [26].…”
Section: Discussionsupporting
confidence: 92%
“…1). In the current study, a decrease in graft size from 2 to 12 weeks was observed in all groups, which was consistent with other studies [28, 29]. The absorption period of dead adipocytes by macrophage phagocytosis within 3 months after transplantation accounts for the atrophy of the grafted fat [26].…”
Section: Discussionsupporting
confidence: 92%
“…The wide variations in the residual graft volumes between mice injected with fat from the same donor also raised questions. Another study found inter-mouse variations for small grafts (0.3 ml) of approximately 8.44 % (Kokai et al, 2017), whereas our results attained an average of 13.8 % variation. A possible explanation for the increased variation may be that the larger size of the graft may result in variable vascularization rate in different animals, leading to uneven inner fat cell survival due to different oxygen and nutrient availability.…”
Section: Discussioncontrasting
confidence: 87%
“…To clarify the effect of hADSC-Exo on adipose graft retention, hADSC-Exo and HFF-Exo were cotransplanted with adipose grafts under the skin of nude mice in this study and observed that hADSC-Exo have a better retention rate than HFF-Exo (Figure 2). Interestingly, we observed that the weight and volume of fat grafts decreased gradually over time in both groups, which could be attributed to the progression of fat grafting, mainly involving cysts, calcification, nodules, fat necrosis, fibrosis, and survival, and eventually stabilization [26,34,35]. In addition, fat number and integrity of adipose grafts were significantly higher in the hADSC-Exo group than in the HFF-Exo group (Figures 3(a) and 3(b)).…”
Section: Discussionmentioning
confidence: 88%